A COMPARATIVE STUDY BETWEEN THE USE OF WHATSAPP AND GOOGLE CLASSROOM IN ENGLISH LEARNING PROCESS - Sri Wahyuni; Yoga Pratama; Ina Lestari (Esteem Journal of English Education Study Programme, 2022)
The objective of the study is to identify the comparison between the use of Whatsapp and Google Classroom in structure class of the English Education Study Program of STKIP Muhammadiyah Pagaralam. This study used descriptive quantitative study method. The population was taken from all students at Second Semester English Education Study Program of STKIP MuhammadiyahPagaralam in the academic year 2020/2021 which has total number of students was 51 students. The sample was taken by using purposive sampling. In taking the sample, the writers used two classes as the WhatsApp group and Google Classroom group. The data were collected using a questionnaire of 20 items for students and 18 items for the structure lecturers’ that designed based on a 5-point Likert scale tocapture things experienced by students and structure lecturers’ and final scored in structure class to identify the effectiveness between using WhatsApp and Google Classroom in teaching learning. The data were analyzed by using descriptive analysis. The writers found that WhatsAppis more effective (85.2%) than Google classroom (53.2%) in developing students’ grammar awareness and creating maximum online learning in structure class. It proved that there was significant differences the effectiveness between using WhatsApp and Google Classroom in Structure Class at Second Semester English Education Study Program of STIKP Muhammadiyah Pagaralam.